Language Shift and Cultural Tapestry: An Observation of Newar Identity in Kirtipur - Gautam, Bhim Lal; Maharjan, Bikram; Poudel, Prem Prasad (Shahid Kirti Multidisciplinary Journal, 2025)
Cultural specificities and their promotion are one of the major concerns in Nepal’s development discourse. While several studies have explored the cultural systems of Nepal’s ethnic/indigenous communities, ethnographic understanding of the values hidden in the micro socio-cultural contexts of Newar community in Kirtipur, one of the core areas of Newar ethnic population in Kathmandu, has yet to get attention. The data in this paper were gathered through multiple sources- questionnaire survey and key informant interviews with 38 participants who had extensive experience in service to education, social and political sectors of Kirtipur municipality. The data were analyzed thematically. The findings of the study suggest that Kirtipur has been shifted to mixed culture because of migration and language contact caused by rapid urbanization, people moving to this city for education and increasing inter-ethnic marriage and family relationships. Not only this, various cultural shifts and modifications are happening with intergenerational language shift with the attraction and interest of cultural ethnicity and identity to the newly developed Newar city Kirtipur. These trends have both linguistic and cultural implications.